Integrative taxonomy of the genus Cyriotasiastes (Newman) (Cerambycidae: Lamiinae) with the description of a new species from Mindanao Island Philippines - Medina, Milton Norman; Lam, Athena W.; Barsevskis, Arvids; Cabras, Analyn A.; Dam, Matthew H. Van (Zootaxa, 2025)
The genus Cyriotasiastes (Neman, 1842) is revised using a combination of morphological, biogeographic, and molecular data. Based on this, we proposed to erect the four species belonging to sub-species Cyriotasiastes rhetenor: C.rhetenor rhetenor, C. rhetenor mindorensis, C. rhetenor panayensis, C. rhetenor solsonanensis, as separate species with the following statuses: Cyriotasiastes rhetenor (Newman, 1842) stat. nov., C. solsonanensis Medina et al., 2023 stat. nov., C. mindorensis Vives, 2009 stat. nov., C.s panayensis Barševskis, 2018 stat. nov. A new species Cyiotasiastes mindanaonis sp. nov. is also described, this is the first record in Mindanao Island and the fifth species for the Philippine fauna. A key to the species in the Philippines is also provided.